ANALISA KINERJA PELAKSANAAN PENAGIHAN PAJAK PADA KPP PRATAMA KAYU AGUNG - Rusmida Jun Harahap H (Fakultas Ekonomi Universitas Tridinanti Palembang, 2014)
ABSTRACTÃ‚Â This research studies about effectivity, coordination, and problem in collecting taxes. Moreover, tax collection performance which is done by KPP Pratama Kayu Agung in tax arrears liquefaction will be measured in this study. Data sample for this study are tax collecting data done by KPP Pratama Kayu Agung in 2010. The data is considered representing the latest tax collectionperformance.This study concludes several things, such : Tax collction performance is ineffective yet, since tax arreas liquefaction does not meet the target. As for the productivity, tax colletionperformance is not optimal yet, because it does not fullfil Standar Prestasi Juru Sita Pajak. Tax Colection internal coordination is fair. In the other hand, the tax collection external coordination has not met the same quality. Wajab Pajak, third party,or tax officer environment it self become problems that create hindrance in collecting taxes.Ã‚Â Keywords : Effectivity, Coordination, Collecting Taxe.